Safety of extended treatment with anakinra in patients with rheumatoid arthritis. Issue 8 (5th January 2006) - Fleischmann, R M; Tesser, J; Schiff, M H; Schechtman, J; Burmester, G-R; Bennett, R; Modafferi, D; Zhou, L; Bell, D; Appleton, B
Abstract : Objective: To determine the safety profile of anakinra after extended exposure in a diverse clinical trial population of patients with rheumatoid arthritis. Methods: A six month, randomised, double blind phase comparing anakinra (100 mg/day) with placebo was followed by open label anakinra treatment for up to three years in patients with rheumatoid arthritis. Concomitant non-steroidal anti-inflammatory drugs, corticosteroids, and other disease modifying antirheumatic drugs were permitted. Results: In all 1346 patients with rheumatoid arthritis received anakinra for up to three years. Patients had varying levels of disease severity, concomitant drug use, and comorbid conditions. Cumulative, exposure adjusted event (EAE) rates for all adverse events (AEs), serious AEs, and deaths were similar during each year of anakinra treatment; the overall rate (0 to 3 years) was similar to that observed for controls during the blinded phase. The most frequent AEs were injection site reactions (122.26 events/100 patient-years), rheumatoid arthritis progression (67.80 events/100 patient-years), and upper respiratory infections (26.09 events/100 patient-years). The EAE rate of serious infections was higher for patients treated with anakinra for 0 to 3 years (5.37 events/100 patient-years) than for controls during the blinded phase (1.65 events/100 patient-years). However, if the patient was not receiving corticosteroid treatment at baseline, the serious infection rate was substantially lower (2.87 event/100 patient-years). The overall incidence of malignancies was consistent with expected rates reported by SEER. Neutralising antibodies developed in 25 patients, but appeared to be transient in 12; neutralising antibody status did not appear related to occurrence of malignancies or serious infections. There were no clinically significant trends in laboratory data related to anakinra. Conclusion: Anakinra is safe and well tolerated for up to three years of continuous use in a diverse population of patients with rheumatoid arthritis.